Effects of emigration on home range and behavior of Atlantic spotted dolphins (Stenella frontalis) - Brittini A. Hill; Denise L. Herzing; Jeremy M. Bono (Academia Biology)
Animals maintain home ranges—areas utilized for gathering food, mating, and caring for offspring—but will relocate when they cannot subsist on resources within their range. Due to climate change, animals are shifting their home ranges more rapidly than in the past. Understanding these changes is an important ecological characteristic of a species and is a priority in informing conservation efforts. In 2013, over half of the resident Atlantic spotted dolphin (Stenella frontalis) community on Little Bahama Bank (LBB) relocated to Great Bahama Bank (GBB), already home to two resident communities of dolphins. We examined the home ranges for LBB residents on LBB (2005–2012), LBB immigrants on GBB (2013–2020), and GBB residents on GBB (2013–2020). Fixed kernel density estimators revealed LBB immigrant dolphins maintained significantly larger home ranges (34–43%) and core areas (42–94%) than both LBB and GBB residents. LBB immigrants were more often found in mixed groups with GBB residents, with the cost of decreased foraging and increased aggression and the benefit of increased courtship. This decreased access to prey may be driving the requirement for larger immigrant home ranges. This is a major finding on how displacement can affect behavior and ranging patterns in a cetacean population.